It's a Woman's World? Occupational Structure and the Rise of Female Employment in Germany - Ronald Bachmann; Gayane Stepanyan (ZBW - Leibniz Information Centre for Economics, 2020)
We analyse whether the rise in female labour force participation in Germany over the last decades can be explained by technological progress increasing the demand for non-routine social and cognitive skills, traditionally attributed to women. We do so by examining which task groups and occupations drive the increase in the female share and how this is related to wages at the individual level. Our findings show that the share of women indeed rises most strongly in non-routine occupations requiring strong social and cognitive skills. While the female share in high-paid occupations increases over time, the share of women in the upper parts of the overall wage distribution rises significantly less.
Keywords: J21; 330; female labour market participation; occupations; tasks; technological progress